The relationship between succession and reclamation of desertified areas in artificial forests of Calligonum spp. in an arid desert of southeastern Iran - Ebrahimi, Mahdieh; Saberi, Morteza (Frontiers in Environmental Science, 2022)
This research investigates the association between the succession and restoring degraded land in the southeast of Iran with artificial Calligonum forests regarding vegetation changes, soil properties, carbon (C) and nitrogen (N) pools in vegetation and soil. Eight forestry sites were selected aging 1, 4, 6, 9, 11, 16, 25, and 30. Observations indicated that vegetation percentage, density, frequency, richness, and diversity of species substantially increased (p<0.01). The highest percentage of vegetation (80.30%), density (62.70 n ha-1), richness (14.15), and diversity (0.90) was observed in the 30-year site. At the end of the succession phase under study (the 25 and 30-year sites), the variation trend of vegetation was steady. As the age of the forests increased, the soil nutrient values increased significantly during succession (p<0.01) even though acidity and electrical conductivity (EC) did not change significantly over time (p>0.01). In the early stages of the succession, the soil's C and N pools (aerial biomass, root, and litter) did not increase significantly (p>0.01). Over time, however, C and N pools of the soil and plants increased (the highest amounts were seen in the 30-year site). The results indicated a significant difference in the soil and vegetation properties in the forestry sites. In general, planting native species and the succession of vegetation can play an effective role in preserving the environment in degraded lands and increasing the C and N pools.